Avoiding dynastic, assortative mating, and population stratification biases in Mendelian randomization through within-family analyses - Ben Brumpton (Nature Portfolio, 2020)
Family-based study designs have been applied to resolve confounding by population stratification, dynastic effects and assortative mating in genetic association analyses. Here, Brumpton et al. describe theory and simulations for overcoming such biases in Mendelian randomization through within-family studies.